MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENDEKATAN PAKEM BERBANTUAN MEDIA PEMBELAJARAN BERBASIS PERMAINAN EDUKASI MONOPOLI PADA PEMBELAJARAN IPS DI KELAS IV SEKOLAH DASAR - Fandaria Abdurrahman; Muhammad Sarlin; Nurainun; Candra Cuga; Samsi Pomalingo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem addressed in this study is: “Can the implementation of the PAKEM approach assisted by Monopoly-based educational game media improve students’ learning outcomes in Social Studies for fourth-grade students at SDN No. 11 Kota Barat, Gorontalo City?” This study employed a Classroom Action Research (CAR) design using data collection techniques consisting of observation, interviews, tests, and documentation. The research subjects were fourth-grade students of SDN No. 11 Kota Barat, Gorontalo City. The findings revealed that students’ learning outcomes improved in each cycle of the study. In the first meeting of Cycle I, out of 11 students, only 5 students achieved the minimum mastery criterion (KKM), representing 45% of the class. In the second meeting of Cycle I, the number of students who achieved mastery increased to 7 students, or 64%. However, the performance indicators and achievement targets had not yet been fulfilled; therefore, the research was continued to Cycle II to further examine the effectiveness of the PAKEM approach and the educational game media employed. In the first meeting of Cycle II, 9 students achieved mastery learning with a percentage of 82%, exceeding the predetermined performance indicator target of 80%. These results indicate a significant improvement in students’ learning outcomes. Therefore, it can be concluded that the implementation of the PAKEM approach assisted by Monopoly-based educational game media effectively improved the Social Studies learning outcomes of fourth-grade students at SDN No. 11 Kota Barat, Gorontalo City.